MENTAL HEALTH IN THE CONTEXT OF CLIMATE CHANGE: ANALYSIS OF THE PSYCHOLOGICAL IMPACTS ON VULNERABLE POPULATIONS - Fillipe Bispo de Oliveira, Estevan; de Figueiredo Moutinho, Bruno; Bromonschenkel De Angeli, Daiany; Musso Rabelo, Luna; Rebonato de Souza Ribeiro, Beatriz; Gomes Santos, Leonardo; Marcelo Pacheco Kokis, João; Costa dos Santos, Mariana; Barcelos Bicalho, Jhennyfer; Wagmacker Barbosa, Bárbara; Frasson Venturini, Lucas; Martineli Lubiana, Lara; et al. (Health and Society, 2024)
Climate change has intensified in recent decades, generating devastating consequences for the environment and, consequently, for human health. Mental health has emerged as a critical area of concern, since extreme weather events such as natural disasters, droughts and floods directly impact the psychological well-being of vulnerable populations. This study aims to analyze how climate change influences mental health, focusing on the psychological effects these changes have on communities in situations of vulnerability. The aim of this analysis is to explore how climate change impacts the mental health of vulnerable populations, discussing the main risk factors involved and addressing strategies that can be adopted to minimize these effects. This discussion is relevant because recognizing the emotional consequences of the climate crisis creates a basis for developing public health practices and psychosocial approaches that promote resilience and adaptation. By focusing on the psychological impact of climate change, we aim to contribute to a more comprehensive and inclusive response to the challenges of a changing world. This is a literature review, based on a qualitative approach, using the Scielo, Google Scholar and PubMed databases. To enhance the research, the health descriptors “climate change”, “mental health”, “psychological impacts” and “solastalgia” were used, with a time frame between 2007 and 2020. The methodology adopted for this analysis consists of a comprehensive literature review, using academic sources and reports from health and environmental organizations. The study addresses how extreme weather events, food insecurity and forced displacement affect mental health, leading to an increase in disorders such as anxiety, depression and post-traumatic stress disorder (PTSD). In addition, the social inequalities that aggravate these impacts are discussed, considering that populations with less access to health resources and services are more susceptible to the adverse effects of climate change. It is concluded that climate change poses a significant threat to mental health, especially for vulnerable populations already facing socio-economic challenges. It is essential that public health policies integrate mental health considerations into climate change adaptation and mitigation strategies. Promoting psychological support programs and implementing targeted interventions can help minimize the negative impacts on mental health, strengthening the resilience of affected communities and promoting a more effective response to climate crises.